Clinical pharmacokinetics of а new original dipeptide anxiolytic GB-115 - V. P. Zherdev; G. B. Kolyvanov; A. A. Litvin; V. V. Smirnov; L. G. Kolik; S. Yu. Raskin; N. Yu. Ivashkina; T. A. Gudasheva; S. B. Seredenin (Фармакокинетика и Фармакодинамика)
Pharmacokinetic study of а new original anxiolytic drug GB-115, developed on the basis of endogenous tetrapeptide cholecystokinin, in healthy volunteers was performed. Volunteers were received drug as single 1, 3, 7, 11 or 15 mg tablets. The parent drug in the human blood plasma was detected within 2-6 hours after ingestion. Cmax/AUC0-T for doses 3-15 mg were averaged 0,482-0,552 h-1. Cmax were averaged from 7,29±2,83 ng/ml (for dose 1 mg) to 44,02±13,23 ng/ml (for dose 15 mg). Half-life of the drug is changed in the range of 0,6-1,0 h. Vd/F amounted to an average of 2,47 l/kg. Summarizing the obtained results it can be concluded that consistent, linear increase in the dose of GB-115 from 1 to 15 mg there is an increase in dose-dependent pharmacokinetic parameters. In the studied range of doses pharmacokinetics of GB-115 was linear.